Addition of malonic esters to azoalkenes generated in situ from α-bromo- and α-chlorohydrazones. (26th October 2021) - Kokuev, Aleksandr O.; Ioffe, Sema L.; Sukhorukov, Alexey Yu.
Graphic abstract: Abstract: Michael addition of malonic esters to azoalkenes generated in situ from α-bromo- and α-chlorohydrazones was accomplished. Both aliphatic and aromatic substrates bearing different functional groups are tolerated. The use of a strong base (sodium hydride) for generation of azoalkenes and deprotonation of malonate was found to be essential for a successful coupling. Synthetic potential of the obtained β-hydrazonoalkylmalonates was demonstrated by their smooth conversion into five- and six-membered N -heterocycles, functionalized hydrazides, 2-(2-oxo-2-arylethyl)malonates and 2-arylethylmalonates.